Carbon Dioxide–Based versus Saline Tissue Expansion for Breast Reconstruction: Results of the XPAND Prospective, Randomized Clinical Trial. Issue 6 (December 2016) - Ascherman, Jeffrey A.; Zeidler, Kamakshi; Morrison, Kerry A.; Appel, James Z.; Berkowitz, R. L.; Castle, John; Colwell, Amy; Chun, Yoon; Johnson, Debra; Mohebali, Khashayar
Abstract : Background: AeroForm is a new type of remote-controlled, needle-free, carbon dioxide–based expander involving a potentially faster method of tissue expansion. Results are presented here from the AirXpanders Patient Activated Controlled Tissue Expander pivotal trial comparing AeroForm to saline tissue expanders. Methods: Women undergoing two-stage breast reconstruction were randomized at 17 U.S. sites in this U.S. Food and Drug Administration–approved investigational device exemption trial. Expansion in the investigational arm was performed by the patient in 10-cc increments up to 30 cc/day of carbon dioxide and in the control arm by the physician with periodic bolus injections of saline. Safety endpoints, expansion and reconstruction times, pain, and satisfaction were assessed. Results: One hundred fifty women were treated: 98 with carbon dioxide expanders ( n = 168) and 52 with saline expanders ( n = 88). The treatment success rate (all breasts exchanged successfully excluding non–device-related failures) was 96.1 percent for carbon dioxide and 98.8 percent for saline. Median time to full expansion and completion of the second-stage operation was 21.0 and 108.5 days (carbon dioxide) versus 46.0 and 136.5 days (saline), respectively, with a similar rate of overall complications. Ease of use for the carbon dioxide expander was rated high by patients (98 percent) and physicians (90 percent). Conclusions: The AirXpanders Patient Activated Controlled Tissue Expander trial results demonstrate that a carbon dioxide–based expander is an effective method of tissue expansion with a similar overall adverse event rate compared to saline expanders, and provides a more convenient and expedient expansion. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, I.